2020
DOI: 10.1186/s12888-020-02564-6
|View full text |Cite
|
Sign up to set email alerts
|

‘I didn’t know what to expect’: Exploring patient perspectives to identify targets for change to improve telephone-delivered psychological interventions

Abstract: Background: Remote delivery of psychological interventions to meet growing demand has been increasing worldwide. Telephone-delivered psychological treatment has been shown to be equally effective and as satisfactory to patients as face-to-face treatment. Despite robust research evidence, however, obstacles remain to the acceptance of telephone-delivered treatment in practice. This study aimed to explore those issues using a phenomenological approach from a patient perspective to identify areas for change in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 36 publications
(53 reference statements)
1
52
0
Order By: Relevance
“…In addition, clarification of patients' expectations and treatment procedures (attendance, cancellation, discharge, confidentiality, environment, and boundaries) should be addressed at the initial assessment and/or early on in treatment to prevent misunderstandings/disappointment as well as to facilitate engagement with telephone treatment. These findings are in line recent findings that identified that patients referred to mental health services are often unaware about remote delivery and have unrealistic expectations of what their treatment might involve [46].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, clarification of patients' expectations and treatment procedures (attendance, cancellation, discharge, confidentiality, environment, and boundaries) should be addressed at the initial assessment and/or early on in treatment to prevent misunderstandings/disappointment as well as to facilitate engagement with telephone treatment. These findings are in line recent findings that identified that patients referred to mental health services are often unaware about remote delivery and have unrealistic expectations of what their treatment might involve [46].…”
Section: Discussionsupporting
confidence: 89%
“…Nearly all articles highlighted the importance of practitioners' qualities and skills (Amos et al, 2019;Bahu, 2019;Christodoulou et al, 2018;Doukani et al, 2020;Farrand et al, 2018;Foy et al, 2019;Goldman et al, 2016;Hadfield et al, 2019;Haller et al, 2019;Leonidaki et al, 2016;Lillevoll et al, 2013;Mackinnon & Murphy, 2016;Millett et al, 2018;Rushton et al, 2020).…”
Section: Practitioners' Perceived Qualities and Skillsmentioning
confidence: 99%
“…Knowledge and understanding of remote treatment are also influencing factors regarding patients attitudes and acceptance towards telephone treatment. Addressing to these two factors, with special focus on existing prejudices and preconceptions about telephone treatment, is key to improve the acceptability with telephone treatment [ 40 , 41 ]. Previous research shows that patients also benefit from telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently cited factors from the patients′ perspective were, for example, user-friendliness, low costs, improved communication, and shorter travel times [ 42 , 43 ]. Important factors influencing patient satisfaction include their overall understanding of telehealth [ 41 ], quality of care received, and telehealth′s convenience [ 44 ]. It is therefore important to support this digital progress and to further establish telemedicine in the health care system.…”
Section: Discussionmentioning
confidence: 99%